Deaf Education: The bilingual linguistic environment as a perspective for bilingual education (Research, Society and Development, 2026)
This study addresses the education of deaf individuals within the global and Brazilian historical context, from Ancient Egypt to contemporary times, with an emphasis on teaching and learning processes from the perspective of bilingual education. The objective is to understand educational policies aimed at deaf education, to contextualize inclusive education within a bilingual approach in the national scenario, and to reflect on the constitution of bilingual linguistic environments as a pedagogical perspective that values Brazilian Sign Language (Libras) and the Portuguese language. This is a qualitative, exploratory study developed through documentary and bibliographic analysis of books, scientific articles, legislation, and materials available in digital media. The analysis of the historical trajectory of deaf education reveals different pedagogical conceptions, political disputes, and social movements advocating for an education that respects cultural and linguistic diversity and promotes the social, cognitive, and identity development of deaf individuals. The results indicate that Art and Technology are relevant resources within the bilingual proposal, contributing to the organization of visually accessible and linguistically inclusive educational environments, as exemplified by the educational products developed. It is concluded that the implementation of bilingual education for deaf individuals still faces structural challenges, requiring the presence of qualified professionals, training in Libras, and the participation of deaf teachers in the constitution of bilingual educational spaces.